Phenomic and genomic landscape of Ethiopian village chickens - Desta, Takele Taye (2015)
This study involves two village chicken populations sampled from Horro and Jarso regions of Western and Eastern Ethiopia respectively. This study maps the phenomic and genomic landscape of the two chicken populations using morphological markers and a high density (600K) SNP array. Although the two chicken populations tend to display nondescript morphological characteristics, they show a subtle variation except for rare morph variants that have been in most instances scored on Jarso chickens. Morphological analysis uncovers a vast array of intrapopulation variation. Genetic diversity and population structure analyses assign the two chicken populations to two distinct genepools representing their population of origin. A high intrapopulation genetic diversity is uncovered, which shows a broad genetic base (high genetic diversity) of the two chicken populations. We hypothesized that a clearly evident genetic divergence observed between the two chicken populations may be attributed to difference in demographic history, origin (routes of introduction to Africa), breeding history of the two chicken populations and demographic structure of subsistence farmers. Absence of gene flow owing to their distant geographic location and ecological variation may have also contributed to this divergence. A population structure analysis performed on a random subset of the two Ethiopian chicken populations along with village chickens sampled from other African countries, Asia and Latin America, commercial populations and the junglefowl species reveals a unique genetic structure of Ethiopian chickens, which implicates the need for further study on the genetic landscape of the latter. To infer the extent of inbreeding we performed a run of homozygosity analysis (ROH). Our analysis indicates that ROH is more intense in Jarso than Horro chickens and in macrochromosomes than microchromosomes. The extensive ROH mapped in some chickens implicates the need to restructure the existing traditional breeding practice of subsistence farmers. Our analysis confirms the commonness of ROH in genic regions. For the first time, we detect twenty three putative uniparental disomy in twenty two Ethiopian village chickens. Signature of selection analysis detects divergently selected genomic regions in the two chicken populations indicating a considerable divergent selection imposed on the two populations. Genes involving in melanogenesis pathway are among those subjected to a divergent selection. However, some overlapping regions were also mapped in the two chicken populations implicating the ubiquitous impact of natural selection on genes regulating vital biological processes. A genome-wide association study performed on pigmentation (earlobe, plumage and shank) traits and variants of crest, comb and a lightly feathered shank maps a number of putative loci that may underlie variations in these traits. Our GWAS analysis on pigmentation traits produced a long list of loci than that have been known to involve in the genetic control of pigmentation in the chicken, with most of these have been mapped in the mouse. We also refined further the causative variants underlying a lightly feathered shank mutation. Our GWAS analysis map a number of putative novel loci that may underlie the genetic control of the traits analysed and this has laid a foundation for subsequent work that would involve targeted sequencing and a candidate gene approach. This study is the first of its kind in Africa that uses a large number of samples and a high density SNP array to unlock phenomic and genomic landscape of the true type village chickens.